Изменения гидратации при образовании комплексов ДНК-лиганд по данным диэлектрометрии - Кашпур, В.А.; Хорунжая, О.В.; Малеев, В.Я. (Доповіді НАН України, 2010)
Для вивчення взаємодiї ДНК з лiгандами пропонується використовувати дiелектричнi вимiрювання в мм дiапазонi. Проведено вимiрювання комплексної дiелектричної проникностi розчинiв ДНК та розчинiв комплексiв ДНК з кофеїном, путресцином i профлавiном. Показано, що утворення комплексiв супроводжується змiною дiелектричних параметрiв та гiдратацiї. The dielectric method in the millimeter range is proposed to study the interaction of nucleic acids with ligands. The measurements of complex dielectric permittivity for solutions of DNA and complexes of DNA with caffeine, putrescine, and proflavine have been carried out. It is shown that the process of complex formation is accompanied by changes of dielectric parameters, as well as by changes of a hydration level.